Designing an Efficient Multimode Environmental Sensor Based on Graphene–Silicon Heterojunction. Issue 4 (27th January 2017) - Shehzad, Khurram; Shi, Tianjin; Qadir, Akeel; Wan, Xia; Guo, Hongwei; Ali, Ayaz; Xuan, Weipeng; Xu, Hua; Gu, Zhongze; Peng, Xinsheng; Xie, Jin; Sun, Litao; et al.
Abstract : By exploiting the adsorbent gaseous molecules induced changes in intrinsic properties of graphene/silicon (Gr/Si) Schottky junction, the authors report a sensitive, low‐power consuming, multimode environmental sensor. By combining an array of Gr/Si Schottky diodes with a differential amplifier circuit, the authors are able to not only differentiate the temperature coefficient and humidity sensing, but also monitor the sun‐light exposure time. Our device is particularly sensitive toward humidity in both forward and reverse biased, and works in resistive as well as capacitive mode. Sensitivity of our devices reached to 17%, 45%, 26%, and 32% per relative humidity (%RH) for reverse biased, forward biased, resistive, and capacitive modes, respectively. In the reverse mode, the power consumption is as low as 2 nW. Moreover, our sensor response is highly selective, with sensitivity lower than 1% for other gases present in atmosphere including H2, O2, N2, and CO2 . High sensitivity, low‐power consumption, multiple operation modes, and high selectivity promises application of our sensor for industrial and home safety, environmental monitoring such as indoor and outdoor air conditions, process monitoring, and others. Abstract : Graphene/silicon Schottky junction is demonstrated as a sensitive, low‐power consuming, multimode environmental sensing platform, which not only differentiates the temperature coefficient and humidity sensing, but also monitors the sun‐light exposure; making it attractive for applications including industrial and home safety, environmental monitoring, process monitoring, etc.